New Insights in PRRT: Lessons From 2021 - Puliani, Giulia; Chiefari, Alfonsina; Mormando, Marilda; Bianchini, Marta; Lauretta, Rosa; Appetecchia, Marialuisa (Frontiers in Endocrinology, 2022)
Peptide receptor radionuclide therapy (PRRT) using radiolabelled somatostatin analogs has been used for over two decades for the treatment of well-differentiated neuroendocrine tumors (NETs) and the publication of the NETTER-1 trials has further strengthened its clinical use. However, many aspects of this treatment are still under discussion. The purpose of this review is to collect and discuss the new available evidence, published in 2021, on the use of 177Lu-DOTATATE or 90Y-DOTATOC in adult patients with NETs focusing on the following hot topics: 1) PRRT use in new clinical settings, broaden its indications; 2) the short- and long-term safety; 3) the identification of prognostic and predictive factors. The review suggests a possible future increase of the PRRT applications, using it in other neuroendocrine tumors, as neoadjuvant treatment or for rechallenge. Regarding safety, available studies, even with long follow-up, supported the low rates of adverse events, even though 1.8% of treated patients developed a second malignancy. Finally, there is a lack of prognostic and predictive factors for PRRT, with the exception of the crucial role of nuclear imaging for both patient selection and treatment response estimation.